GAMBARAN TINGKAT PENGETAHUAN, SIKAP DAN PERILAKU MAHASISWA UNIVERSITAS PATTIMURA TENTANG PENGGUNAAN HELM SEBAGAI UPAYA MENGURANGI CEDERA KEPALA AKIBAT KECELAKAAN LALU LINTAS DI KOTA AMBON - Glaselaria Angelin Oeijano; Ivanmorl Ruspanah; Laura Bianca Sylvia Huwae (Fakultas Kedokteran Universitas Pattimura, 2023)
Traffic accidents (KLL) are the first cause of death for children and young adults aged 5-29 years. Indonesia is in the Southeast Asia region which ranks second with the highest traffic accident rate of 20.7/100,000 people. Motorcycles are the biggest contributor due to the minimum level of safety which results in head injuries and causes death, permanent disability, and other organ defects. Therefore, it is necessary to use personal protective equipment in crossing traffic, namely helmets to minimize the risk of death. This study aims to describe the level of knowledge, attitudes and behavior of Pattimura University students regarding the use of helmets as an effort to reduce head injuries due to traffic accidents in Ambon city. This research used a cross-sectional quantitative descriptive method. A sample of 108 respondents was taken by simple random sampling. Data obtained from the results of filling out the questionnaire. The results showed that 59 (54.6%) respondents had sufficient knowledge, 57 (52.8%) respondents confirmed positively and 57 (52.8%) respondents often used helmets when crossing traffic.